Strategy, innovation and internationalization processes: in search of useful synergies - Barbosa, Fernando (2016)
Globalization of the economy has revived the interest on the theme of internationalization of companies. There may be several motives for a company to expand its markets, but whatever they are, the success of the process depends on specific and characteristic assets that the company possesses and on their capacity to provide competitive muscle. Among other strategic choices, the development of innovation capabilities is a possible path to provide the firm with knowledge and organizational assets that confer it a competitive edge. Knowledge assets are increasingly important in an interconnected and open world market, where traditional localized competitive factors, such as low labour costs, are rapidly losing appeal as drivers of sustainable and continued value creation. In a highly competitive international market, innovation and internationalization seem to be themes that are intrinsically related to each other, in the sense that knowledge and innovation capabilities seem to be a necessary prerequisite to an internationalization process. However, per se, innovation capabilities, and the assets behind it, may not be enough to a successful endeavour. In the absence of privileged, localized knowledge of the national market, strategic considerations are of paramount importance to the internationalization process. Strategic actions are important, not only at the planning stage but also at the implementation stage. It is argued in this paper that these aspects, knowledge, innovation and strategy, are crucial to understand actual internationalization processes and dynamics. This paper intends to examine the above concepts and the links between these factors and their effects on business performance and competitiveness and comprehend internationalization processes. It provides a comprehensive review on the literature regarding the possible connections between the three concepts and it identifies the main ideas and variables that have been suggested and are being regarded. It provides a useful synthesis and it suggests f